Improving the Ability of Second Grade Students in Writing Words by Using Upright Notebook Media - Marsih Priyanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to improve the abilityof class II students at SD Negeri Jombor Ceper District,Klaten Regency in writing word using 5 striped book media.This reseach design which is carried out in two cycles through the same stages,namely planning implementation,observation and reflection.This research was carried out in class II of SD Negeri Jombor,Ceper District,Klaten Regency with a total of 13 students consisting of 5 male students and 8 female students.The data collection techniques used were observation and evaluation.The collected data analyzed using  qualitative and quantitative analysis techniques.The results of the reseach showed that by using 5 striped book media,learning  active became more enjoyable so that student learning outcomes increased namely the results from cycle l to cycle II there was an increase.In cycle I the average score obtained by students was 64,33 with a classical completion levevl of 45%,the incomplete score obtained by students was 85,67 with a level of classical completeness becomes 90% resulting in an increase in classicalcompleteness of 50%.From these result it can be conluded that the use of can improve the word writing ability of class II students at SD N Jombor.